A copper(ii)-catalyzed three-component reaction of aryldiazonium tetrafluoroborates, sulfur dioxide, with alkenes. Issue 11 (13th September 2016) - Mao, Runyu; Yuan, Zheng; Zhang, Rui; Ding, Yechun; Fan, Xiaona; Wu, Jie
Abstract : A three-component reaction of aryldiazonium tetrafluoroborates, sulfur dioxide, with alkenes catalyzed by copper(ii ) bromide is developed, which provides an efficient route to ( E )-alkenyl sulfones or allylic sulfones via the insertion of sulfur dioxide. Abstract : A three-component reaction of aryldiazonium tetrafluoroborates, sulfur dioxide, with alkenes catalyzed by copper(ii ) bromide is developed, which provides an efficient route to ( E )-alkenyl sulfones or allylic sulfones via the insertion of sulfur dioxide. A radical process is believed to be involved in the reaction.